Replacing sodium bicarbonate with half amount of calcareous marine algae in the diet of beef cattle - Sgoifo Rossi, Carlo Angelo; Compiani, Riccardo; Baldi, Gianluca; Taylor, Stephen J.; Righi, Federico; Simoni, Marica; Quarantelli, Afro (Brazilian Journal of Animal Science, 2019)
This study evaluated the effects of feeding calcareous marine algae or sodium bicarbonate as rumen buffer on the performance, behaviour, in vitro diet digestibility, and meat quality of beef cattle. A total of 180 Charolaise bullocks (536±38 kg; 14±1 months of age) were divided into two homogeneous groups and fed a diet with a mineral mix containing 40% sodium bicarbonate or 20% calcareous marine algae (CMA) for the entire fattening period (130 days). Of the in vivo and in vitro parameters evaluated, CMA supplementation improved average daily gain and feed conversion ratio and reduced the prevalence of bloat and lameness. Bullocks fed CMA tended to exhibit a calmer behaviour while in the pen. Supplementation with CMA improved rumen pH and in vitro digestion. Meat from bullocks fed CMA showed a lower pH and higher lightness and tenderness. The results suggest that CMA is more effective than sodium bicarbonate in buffering beef cattle, with a positive impact on growth performance, feed efficiency, health, and meat quality
Keywords: acidosis; buffer; behavior; digestibility; lithothamnium; meat quality